The Direct Method in Improving Arabic Conversation Skills at MTs - Su'udin Aziz (Badan Usaha Milik Desa Berkaho Pungpungan, 2025)
The limited speaking ability of students in learning Arabic at MTs Islahiyah Kalitidu indicates the need for an effective instructional method that supports oral communication skills. This study aims to analyze the implementation of the Direct Method in enhancing students’ Arabic speaking proficiency, as well as to identify students’ responses and the challenges encountered during the learning process. A qualitative descriptive approach was employed, with data gathered through classroom observations, semi-structured interviews with teachers and students, and documentation analysis. The results show that the Direct Method was applied by maximizing the use of Arabic as the primary medium of communication, minimizing translation, and encouraging vocabulary application in contextual situations. Repetition, role-playing, questioning techniques, and visual media were used to stimulate active student participation. Students demonstrated positive responses, supported by improvements in fluency, pronunciation, and confidence in speaking Arabic. Peer interaction also contributed to a more cooperative learning atmosphere. Despite these positive developments, several challenges were identified, including students’ limited vocabulary mastery, differences in proficiency levels, large class sizes, and limited learning facilities. However, adaptive strategies such as contextual learning, scaffolding techniques, and visual reinforcement helped mitigate these constraints. The study concludes that the Direct Method is effective in improving Arabic speaking skills when supported by competent teaching practices and adequate learning resources. Strengthening teacher professional development, integrating technology, and applying differentiated instruction are recommended to optimize the implementation of the Direct Method in Arabic language education